1999
DOI: 10.1111/j.1540-8159.1999.tb00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Formulae for Heart Rate Correction of QT Interval in Exercise Electrocardiograms

Abstract: The study investigated the differences in five different formulae for heart rate correction of the QT interval in serial electrocardiograms recorded in healthy subjects subjected to graded exercise. Twenty-one healthy subjects (aged 37+/-10 years, 15 male) were subjected to graded physical exercise on a braked bicycle ergometer until the heart rate reached 120 beats/min. Digital electrocardiograms (ECG) were recorded on baseline and every 30 seconds during the exercise. In each ECG, heart rate and QT interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 8 publications
5
52
0
Order By: Relevance
“…Many workers have investigated the relationship of the QT/RR relationship during exercise [4,6,[13][14][15]. As with all of these studies, we have also shown a linear relationship between the QT and RR interval, even though different mathematical models across the studies have been used.…”
Section: Figuresupporting
confidence: 54%
“…Many workers have investigated the relationship of the QT/RR relationship during exercise [4,6,[13][14][15]. As with all of these studies, we have also shown a linear relationship between the QT and RR interval, even though different mathematical models across the studies have been used.…”
Section: Figuresupporting
confidence: 54%
“…[13][14][15] This alteration of the repolarization period could be documented in all available ECGs recorded at different time points and ages, with a QT interval always Ͻ300 ms, without significant dynamic changes during heart rate variations or on exertion. QT interval constantly Յ300 was regarded as short QT.…”
Section: Discussionmentioning
confidence: 99%
“…That is met using adapted derivation leads and a matched window. A refinement to a fixed window definition would be to adapt its position using the Bazett correction or any Q-T predictor [32], [33].…”
Section: Discussionmentioning
confidence: 99%